Analysis of Law No. 24 of 2004 on the Non-Participation of Baitul Maal Wal Tamwil as Deposit Insurance Corporation Participants - Lubis, Rahmat Husein; Nurlaeli, Ida (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
This research originates from statutory regulation number 24 of 2004 regarding the Deposit Insurance Corporation. The existence of these statutory regulations provides a sense of certainty for every customer in carrying out financing and savings activities at Islamic financial institutions. However, not all Islamic financial institutions are registered as members of deposit insurance institutions. One of them is an Islamic financial institution, Baitul Maal Wal Tamwil (BMT). Whereas in the Baitul Maal Wal Tamwil (BMT) there is customers' money that must be ensured for their savings deposits. Baitul Maal Wal Tamwil (BMT) Assyafi'yah, for example, in his financial reports from 2019 to 2021 has a large amount, in 2019 with a total deposit of Rp. 14,790,416,786, in 2020 with a total deposit of Rp.15,494,878,688, and in 2021 with a total deposit of Rp. 15,900,496,978. From the data above, it can be seen that in Baitul Maal Wal Tamwil (BMT) Assyafi'yah itself, the number of customer deposits increases every year but are still not registered as a deposit insurance institution. This research is a type of library research with the nature of descriptive qualitative research with a normative juridical approach. Research with the type of research library research is research with primary data sources and secondary data using a book, journal, or other scientific works related to this research and Law No. 24 of 2004 concerning Deposit Insurance Corporation. In the concluding part, the researcher will describe in narrative form why Baitul Maal Wal Tamwil (BMT) has not been registered as a participant in a deposit insurance institution.